2019
DOI: 10.5937/savteh1901033m
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anions on decolorization of textile azo dye Reactive Orange 16 with UV/H2O2 process

Abstract: The effects of various organic and inorganic anions on decolorization of textile dye Reactive Orange 16 by means of hydroxyl radicals have been studied. These anions are commonly present in wastewaters from textile industry and include chloride, sulfate, carbonate/bicarbonate, nitrate and acetate anions. The experiments were conducted in the presence of different concentrations of anions and at different initial pH values in a batch photoreactor equipped with UV-C (254 nm) lamps in the presence of hydrogen per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…At higher pH values, an increase in the concentration of OH À ions on the adsorbent's surface led to repulsion between the adsorbent and the methyl red dye, decreasing the adsorption capacity. 62 On the other hand, adsorption capacity decreased at acidic pH due to the dissolution of the adsorbent at lower pH values.…”
Section: Paper Materials Advancesmentioning
confidence: 99%
“…At higher pH values, an increase in the concentration of OH À ions on the adsorbent's surface led to repulsion between the adsorbent and the methyl red dye, decreasing the adsorption capacity. 62 On the other hand, adsorption capacity decreased at acidic pH due to the dissolution of the adsorbent at lower pH values.…”
Section: Paper Materials Advancesmentioning
confidence: 99%
“…Therefore, around 17-20% of industrial wastewater originates only from the textile industries [7,8]. From an environmental point of view, dye effluents can lead to adverse effects on aquatic life, plant life as well as on public health [6,[9][10][11]. However, it has been reported that many organic dyes are extremely difficult to degrade by conventional wastewater treatment plants due to their stable chemical structures (e.g., aromatic rings) [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…AOPs are known to generate hydroxyl radical (HO), which is well known as a powerful oxidant with an oxidation potential of around 2.86 V [12,17,18]. HO can react and degrade almost all the nonbiodegradable stable organic compounds via abstraction of hydrogen bond, electrophilic addition and electron transfer reactions [10,18,19]. Many authors have reported that the reactivity of non-selective HO towards most of the organic substrates in the range of 10 6 -10 10 M −1 s −1 , which of course depends on the nature of the target pollutants [10,17,18,20,21].…”
Section: Introductionmentioning
confidence: 99%